Evaluation of Engineering Training Competences in the Field of Smart Systems as a Factor of Russian Innovative Development Through the Example of Tomsk Polytechnic University; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Ardashkin I. B. Igor Borisovich (2017, 2017)
Title screen